Lipoxygenase and Hyaluronidase Inhibitory Activities of Constituents from Phyllagathis rotundifolia and Carallia brachiata - S.K, Ling,; T, Tanaka,; I, Kouno, (Malaysian Journal of Science, 2005)
Lipoxygenase is known to be responsible for a number of pathophysiological processes such as asthma, psoriasis, cancer metastasis and artherosclerosis, while hyaluronidase is involved in allergic effects, migration of cancer cells, inflammation and the increase in permeability of vascular system. There is considerable interest in searching for compounds that can inhibit the activities of these enzymes. As part of the chemical studies on medicinal plants of Malaysia, we have isolated a total of 50 compounds from Phyllagathis rotundifolia (Melastomataceae) and Carama brachiata (Rhizophoraceae), including eight compounds which were new. Twenty-five of the isolated compounds were evaluated for their inhibitory effects on lipoxygenase and hyaluronidase activities. The relationship between the number of phenol groups on the test compounds and their IC₅₀ values were also investigated.